Diseño de tratamiento de un efluente proveniente del beneficio de la industria avícola (2017)
The present work aims to propose a treatment system and to expose its conceptual design for the poultry benefit industry, which allows them to comply with legislation 631 of 2015, as well as to reduce the flow of dumping, implementing practices of recirculation, Reuse and reduction of water consumption used in the production process. This is achieved by measuring the water consumption of the entire plant, identifying and evaluating the points of greatest consumption and its potential for reuse and recirculation without reconditioning, respecting hygiene laws for the food industry.